Strategy For Implementing Al-Qur'an Guidance In Improving The Quality Of Islamic Education - Sadan Sadan (Doctoral Program of Social Science Pasundan University, 2026)
Qur'anic development is one of the main pillars in the implementation of integrated Islamic education. SMPIT Al-Mufid positions Qur'anic development as a flagship program to enhance the quality of Islamic education in academic, spiritual, and character dimensions. This study aims to analyze the implementation strategies of Qur'anic development at SMPIT Al-Mufid and its contribution to improving the quality of Islamic education. This research employs a qualitative approach with a case study design. Data were collected through observations, in-depth interviews with the principal, tahfizh and tahsin teachers, and documentation analysis. The findings reveal that the implementation strategies include integrated curriculum planning, systematic habituation of Qur'an reading and memorization, continuous teacher competency development, and ongoing evaluation of students' achievements. These strategies positively impact students' Qur'anic literacy, memorization achievements, religious discipline, and character formation. The study concludes that well-planned, sustainable, and integrated Qur'anic development significantly contributes to improving the quality of Islamic education at SMPIT Al-Mufid. The results are expected to serve as a reference for other Islamic schools in developing effective Qur'anic programs.